2018
DOI: 10.1152/ajprenal.00498.2017
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal activation of endothelin type B receptors improves kidney oxygenation in type 1 diabetic rats

Abstract: About one-third of patients with type 1 diabetes develops kidney disease. The mechanism is largely unknown, but intrarenal hypoxia has been proposed as a unifying mechanism for chronic kidney disease, including diabetic nephropathy. The endothelin system has recently been demonstrated to regulate oxygen availability in the diabetic kidney via a pathway involving endothelin type A receptors (ETA-R). These receptors mainly mediate vasoconstriction and tubular sodium retention, and inhibition of ETA-R improves in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
(38 reference statements)
1
2
0
Order By: Relevance
“…Our data showed that hypoxia down-regulates ENDRB gene expression and that inhibition of ERN1 signaling leads to up-regulation of this gene. These results conform to data that intrarenal activation of endothelin type B receptors improve kidney oxygenation in type 1 diabetic rats and that pharmacological inhibition and cardiac-specific knockout of endothelin receptor type B lead to cardiac resistance to extreme hypoxia (Franzen et al 2018;Stobdan et al 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Our data showed that hypoxia down-regulates ENDRB gene expression and that inhibition of ERN1 signaling leads to up-regulation of this gene. These results conform to data that intrarenal activation of endothelin type B receptors improve kidney oxygenation in type 1 diabetic rats and that pharmacological inhibition and cardiac-specific knockout of endothelin receptor type B lead to cardiac resistance to extreme hypoxia (Franzen et al 2018;Stobdan et al 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Kidney function (data presented in the Electronic Supplementary Material (ESM) Table S1 ) was determined in parallel in both control and diabetic animals ( n = 4/group) as previously described [ 16 ]. In brief, anaesthesia was induced using thiobutabarbital and body temperature maintained at 37.5 °C using a servo-controlled heating pad.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, ET B receptor-null mice retain water and Na ϩ , likely because of the abolition of effects of ET on aldosterone-sensitive collecting duct cells (16). Also, recent experimental data suggest that ET B receptor signaling in the diabetic kidney improves intrarenal tissue oxygenation (15). Hence, the most likely successful drug candidate would be a highly selective antagonist of ET A receptors (21).…”
Section: Introductionmentioning
confidence: 99%